2014
DOI: 10.1177/1049909114542647
|View full text |Cite
|
Sign up to set email alerts
|

The Preference of Place of Death and its Predictors Among Terminally Ill Patients With Cancer and Their Caregivers in China

Abstract: This study described information about the preference of place of death and its potential predictive factors in terminally ill patients with cancer in mainland of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 17 publications
1
90
5
2
Order By: Relevance
“…However, there are few studies that investigates the associations between preference for home death and level of education 32 . Previous research in Ibiza 33 and China 34 showed that low educational attainment is associated with a greater preference for death at home and those with higher attainment prefer to die in institutions 32 . Our results point to a contrary association.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are few studies that investigates the associations between preference for home death and level of education 32 . Previous research in Ibiza 33 and China 34 showed that low educational attainment is associated with a greater preference for death at home and those with higher attainment prefer to die in institutions 32 . Our results point to a contrary association.…”
Section: Discussionmentioning
confidence: 92%
“…The palliative care needs were developed by the research based on literature reviews consisting of 13 items. It asks about different of needs: information (item 1-3), physical (item 4-7), emotional/spiritual (items 8-10) and social supports (item [11][12][13]. Each item represents one need of cancer patients and scale was rated on a scale from 1 (not importance) to 5 (very importance).…”
Section: Measurementmentioning
confidence: 99%
“…The ultimate goal is to provide patients and families with the best QOL during the trajectory of diseases [11]. The data from previous studies showed that many terminally ill patients would prefer to stay and die in their own homes, but unfortunately some of patients may not be able to do so [11][12][13][14]. Evidence has presented many benefits of home care for palliative care patients.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated possible associations between preference for home death and demographic, socio-economic and disease-related factors. It has been found that being male, living with a partner and having a lower level of education were associated with a higher preference for dying at home (1,(11)(12)(13). Regional differences were also found as people living in rural areas tend to have a higher preference for home death (13,14).…”
Section: Introductionmentioning
confidence: 99%